Price discovery and market reflexivity in agricultural futures contracts with different maturities - Steffen Volkenand; Günther Filler; Martin Odening (Risks, 2020)
The purpose of this paper is to analyze market reflexivity in agricultural futures contracts with different maturities. To this end, we apply a four-dimensional Hawkes model to storable and non-storable agricultural commodities. We find market reflexivity for both storable and non-storable commodities. Reflexivity accounts for about 50 to 70% of the total trading activity. Differences between nearby and deferred contracts are less pronounced for non-storable than for storable commodities. We conclude that the co-existence of exogenous and endogenous price dynamics does not change qualitative characteristics of the price discovery process that have been observed earlier without the consideration of market reflexivity.
Keywords: G14; C49; 330; agricultural commodity futures; price discovery; market reflexivity; Hawkes process